Penilaian Formatif Menggunakan Quizizz Untuk Meningkatkan Hasil Belajar Di Sekolah Dasar - Wasilatul Ibad (JIEES : Journal of Islamic Education at Elementary School, 2023)
Technology has now affected every aspect of human life, one of which is education. Technology is expected to improve problems in learning and teaching in education. This study will examine the effectiveness of Quizizz in improving student learning outcomes in elementary schools. This research is a mixed-methods, multiphase design with 30 research samples at SD Khadijah Surabaya. The main finding in this study is that quiz-based assessment is able to facilitate the tasks of teachers and students in carrying out evaluations. Furthermore, Quizizz can improve student learning outcomes in elementary schools. This is supported by the percentage of student success, which increased from 56% to 76%, and also based on the results of the analysis using the T-test that has been carried out using the SPSS version 20 computer program, which shows the significance value of the t test < 0.05, so that H0 is rejected and H1 is accepted. In conclusion, Quizizz can be applied to formative assessment and effectively improve student learning outcomes in elementary schools.